STUDI WAKTU TUNGGU PELAYANAN RAWAT JALAN DI RUMAH SAKIT UMUM DAERAH YOWARI JAYAPURA - Rusli Rusli (UNUSA Press, 2018)
Timeliness of service was a common problem that occured in outpatient installations. The purpose of this study was to identify the waiting time of outpatient service in Yowari Jayapura General Hospital. The study observed and interviewed 379 respondents randomly from May to June 2015. Location of study was registration counter, pharmacy and 4 polyclinics (child, obstetrics, interna and surgery). The study found the waiting time in registration counter was 14 minutes. Meanwhile, the waiting time of each polyclinic was varied. The fastest waiting time occured in child polyclinic (48 minutes) and longest in obstetric polyclinic (58 minutes). Waiting time for pharmacyservice was differentiated by type of recipe where for non pooker recipe type was 14 minutes, while puyer was 34 minutes. This study recommended the addition of the number of health workers to encourage the service process so as to support the effectiveness and satisfaction for the community.